Professional Societies and Ecologically Based Pest Management: Proceedings of a Workshop - National Research Council (The National Academies Press, 2000)
The National Research Council's (NRC) Board on Agriculture and Natural Resources invited professional societies associated with agriculture and ecology to participate in a two-day workshop to explore leadership and a common vision for ecologically based pest management (EBPM). These proceedings describe the challenges of and opportunities for EBPM discussed by participants in the workshop.

Changes in the Sheep Industry in the United States: Making the Transition from Tradition - National Research Council
The U.S. sheep industry is complex, multifaceted, and rooted in history and tradition. The dominant feature of sheep production in the United States, and, thus, the focus of much producer and policy concern, has been the steady decline in sheep and lamb inventories since the mid-1940s. Although often described as \

The Future Role of Pesticides in US Agriculture - National Research Council
Although chemical pesticides safeguard crops and improve farm productivity, they are increasingly feared for their potentially dangerous residues and their effects on ecosystems. The Future Role of Pesticides explores the role of chemical pesticides in the decade ahead and identifies the most promising opportunities for increasing the benefits and reducing the risks of pesticide use. The committee recommends R&D, program, and policy initiatives for federal agriculture authorities and other stakeholders in the public and private sectors. This book presents clear overviews of key factors in chemical pesticide use, including: Advances in genetic engineering not only of pest-resistant crops but also of pests themselves. Problems in pesticide use2014concerns about the health of agricultural workers, the ability of pests to develop resistance, issues of public perception, and more. Impending shifts in agriculture2014globalization of the economy, biological \

Emerging Technologies to Benefit Farmers in Sub-Saharan Africa and South Asia - National Research Council (The National Academies Press, 2009)
Increased agricultural productivity is a major stepping stone on the path out of poverty in sub-Saharan Africa and South Asia, but farmers there face tremendous challenges improving production. Poor soil, inefficient water use, and a lack of access to plant breeding resources, nutritious animal feed, high quality seed, and fuel and electricity-combined with some of the most extreme environmental conditions on Earth-have made yields in crop and animal production far lower in these regions than world averages. Emerging Technologies to Benefit Farmers in Sub-Saharan Africa and South Asia identifies sixty emerging technologies with the potential to significantly improve agricultural productivity in sub-Saharan Africa and South Asia. Eighteen technologies are recommended for immediate development or further exploration. Scientists from all backgrounds have an opportunity to become involved in bringing these and other technologies to fruition. The opportunities suggested in this book offer new approaches that can synergize with each other and with many other activities to transform agriculture in sub-Saharan Africa and South Asia.

Evaluating the Effectiveness of Fish Stock Rebuilding Plans in the United States - National Research Council (The National Academies Press, 2014)
In the United States (U.S.), the Fishery Conservation and Management Act of 1976, now known as the Magnuson-Stevens Fishery Conservation and Management Act (MSFCMA), was the first major legislation to regulate federal fisheries in the U.S. Fishery Conservation Zone (later designated as the U.S. exclusive economic zone). The re-authorization of the MSFCMA passed by Congress in 2006 included additional mandates for conserving and rebuilding fish stocks and strengthening the role of scientific advice in fisheries management. Approximately 20% of the fisheries that have been assessed are considered overfished according to the September 2012 stock status Report to Congress prepared by the U.S. National Oceanic and Atmospheric Administration (NOAA). Overfished refers to a stock that is below the minimum stock size threshold, commonly set to half the stock size at which maximum sustainable yield (MSY) is achieved. Under the provisions of the MSFCMA, rebuilding plans for overfished stocks should take no more than 10 years, except when certain provisions apply. Rebuilding mandates have led to substantial reductions in catch and effort for many fisheries, raising concerns about the consequent social and economic impacts to the fishing communities and industry. Evaluating the Effectiveness of Fish Stock Rebuilding Plans in the United States reviews the technical specifications that underlie current federally-implemented rebuilding plans, and the outcomes of those plans. According to this report, fisheries management has evolved substantially since 1977 when the U.S. extended its jurisdiction to 8 200 miles, in the direction of being more prescriptive and precautionary in terms of preventing overfishing and rebuilding overfished fisheries. However, the trade-offs between precaution and yield have not been fully evaluated. Evaluating the Effectiveness of Fish Stock Rebuilding Plans in the United States discusses the methods and criteria used to set target fishing mortality and biomass levels for rebuilding overfished stocks, and to determine the probability that a particular stock will rebuild by a certain date. This report will be of interest to the fishing industry, ecology professionals, and members of Congress as they debate the renewal of the Magnuson-Stevens Fishery Conservation and Management Act.

Animal Research in a Global Environment: Meeting the Challenges: Proceedings of the November 2008 International Workshop - National Research Council (The National Academies Press, 2011)
Animal research will play an essential role in efforts to meet increasing demands for global health care. Yet the animal research community faces the challenge of overcoming negative impressions that industry and academia engage in international collaborations in order to conduct work in parts of the world where animal welfare standards are less stringent. Thus, the importance of ensuring the international harmonization of the principles and standards of animal care and use cannot be overstated. A number of national and international groups are actively working toward this goal. The Institute for Laboratory Animal Research (ILAR), a program unit of the US National Research Council, is committed to promoting both the welfare of animals used in research and the quality of the resulting science. In 2008, to follow up on the 2003 event, ILAR convened a workshop which brought together 200 participants from 17 countries. Their mission was to identify and promote better understanding of important challenges in the conduct of animal research across country boundaries. These challenges include: the sourcing of animals; the quality of veterinary care; competent staff; the provision of a suitable environment (including nutritious food and potable water) for animals; and ongoing oversight of the animal program; among others. Animal Research in a Global Environment summarizes the proceedings of the 2008 workshop. The impact of this 2008 workshop has extended beyond the oral presentations conveyed in these proceedings. It has been a vital bridge for diverse colleagues and organizations around the world to advance initiatives designed to fill gaps in standards, professional qualifications, and coordination of animal use.

Improving Data Collection and Measurement of Complex Farms - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
America2019s farms and farmers are integral to the U.S. economy and, more broadly, to the nation2019s social and cultural fabric. A healthy agricultural sector helps ensure a safe and reliable food supply, improves energy security, and contributes to employment and economic development, traditionally in small towns and rural areas where farming serves as a nexus for related sectors from farm machinery manufacturing to food processing. The agricultural sector also plays a role in the nation2019s overall economic growth by providing crucial raw inputs for the production of a wide range of goods and services, including many that generate substantial export value. If the agricultural sector is to be accurately understood and the policies that affect its functioning are to remain well informed, the statistical system2019s data collection programs must be periodically revisited to ensure they are keeping up with current realities. This report reviews current information and makes recommendations to the U.S. Department of Agriculture2019s (USDA2019s) National Agricultural Statistics Service (NASS) and Economic Research Service (ERS) to help identify effective methods for collecting data and reporting information about American agriculture, given increased complexity and other changes in farm business structure in recent decades.

Advancing Prion Science: Guidance for the National Prion Research Program - Institute of Medicine (The National Academies Press, 2004)
In Advancing Prion Science, the Institute of Medicine2019s Committee on Transmissible Spongiform Encephalopathies Assessment of Relevant Science recommends priorities for research and investment to the Department of Defense2019s National Prion Research Program (NPRP). Transmissible spongiform encephalopathies (TSEs), also called prion diseases, are invariably fatal neurodegenerative infectious diseases that include bovine spongiform encephalopathy (commonly called mad cow disease), chronic wasting disease, scrapie, and Creutzfeldt-Jakob disease. To develop antemortem diagnostics or therapies for TSEs, the committee concludes that NPRP should invest in basic research specifically to elucidate the structural features of prions, the molecular mechanisms of prion replication, the mechanisms of TSE pathogenesis, and the physiological function of prions2019 normal cellular isoform. Advancing Prion Science provides the first comprehensive reference on present knowledge about all aspects of TSEs2014from basic science to the U.S. research infrastructure, from diagnostics to surveillance, and from prevention to treatment.

Biosolids Applied to Land: Advancing Standards and Practices - National Research Council (The National Academies Press, 2002)
The 1993 regulation (Part 503 Rule) governing the land application of biosolids was established to protect public health and the environment from reasonably anticipated adverse effects. Included in the regulation are chemical pollutant limits, operational standards designed to reduce pathogens and the attraction of disease vectors, and management practices. This report from the Board on Environmental Studies and Toxicology evaluates the technical methods and approaches used by EPA to establish those standards and practices, focusing specifically on human health protection. The report examines improvements in risk-assessment practices and advances in the scientific database since promulgation of the regulation, and makes recommendations for addressing public health concerns, uncertainties, and data gaps about the technical basis of the biosolids standards.

Exploring Health and Environmental Costs of Food: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2012)
The U.S. food system provides many benefits, not the least of which is a safe, nutritious and consistent food supply. However, the same system also creates significant environmental, public health, and other costs that generally are not recognized and not accounted for in the retail price of food. These include greenhouse gas (GHG) emissions, soil erosion, air pollution, and their environmental consequences, the transfer of antibiotic resistance from food animals to human, and other human health outcomes, including foodborne illnesses and chronic disease. Some external costs which are also known as externalities are accounted for in ways that do not involve increasing the price of food. But many are not. They are borne involuntarily by society at large. A better understanding of external costs would help decision makers at all stages of the life cycle to expand the benefits of the U.S. food system even further. The Institute of Medicine (IOM) and the National Research Council (NRC) with support from the U.S. Centers for Disease Control and Prevention (CDC) convened a public workshop on April 23-23, 2012, to explore the external costs of food, methodologies for quantifying those costs, and the limitations of the methodologies. The workshop was intended to be an information-gathering activity only. Given the complexity of the issues and the broad areas of expertise involved, workshop presentations and discussions represent only a small portion of the current knowledge and are by no means comprehensive. The focus was on the environmental and health impacts of food, using externalities as a basis for discussion and animal products as a case study. The intention was not to quantify costs or benefits, but rather to lay the groundwork for doing so. A major goal of the workshop was to identify information sources and methodologies required to recognize and estimate the costs and benefits of environmental and public health consequences associated with the U.S. food system. It was anticipated that the workshop would provide the basis for a follow-up consensus study of the subject and that a central task of the consensus study will be to develop a framework for a full-scale accounting of the environmental and public health effects for all food products of the U.S. food system. Exploring Health and Environmental Costs of Food: Workshop Summary provides the basis for a follow-up planning discussion involving members of the IOM Food and Nutrition Board and the NRC Board on Agriculture and Natural Resources and others to develop the scope and areas of expertise needed for a larger-scale, consensus study of the subject.

Assessing Equity in the Distribution of Fisheries Management Benefits: Data and Information Availability - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Fisheries are essential to the global economy and feed billions around the world; they, support individuals and communities, and sustain cultural heritages and livelihoods. Although U.S. fisheries have been managed for commercial fishing historically, there has been an interest more recently in better accounting for and meeting the needs of the diverse individuals, groups, and communities that rely on and participate in fisheries, or aspire to do so. At the request of the National Marine Fisheries Service, this report considers information needs and data collection for assessing the distribution of fisheries management benefits. Assessing Equity in the Distribution of Fisheries Management Benefits identifies information needs, obstacles to collecting information, and potential methodologies for assessing where and to whom the primary benefits of commercial and for-hire fishery management accrue.

Status of Pollinators in North America - National Research Council (The National Academies Press, 2007)
Pollinators2014insects, birds, bats, and other animals that carry pollen from the male to the female parts of flowers for plant reproduction2014are an essential part of natural and agricultural ecosystems throughout North America. For example, most fruit, vegetable, and seed crops and some crops that provide fiber, drugs, and fuel depend on animals for pollination. This report provides evidence for the decline of some pollinator species in North America, including America's most important managed pollinator, the honey bee, as well as some butterflies, bats, and hummingbirds. For most managed and wild pollinator species, however, population trends have not been assessed because populations have not been monitored over time. In addition, for wild species with demonstrated declines, it is often difficult to determine the causes or consequences of their decline. This report outlines priorities for research and monitoring that are needed to improve information on the status of pollinators and establishes a framework for conservation and restoration of pollinator species and communities.

Genetically Engineered Crops: Experiences and Prospects - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Genetically engineered (GE) crops were first introduced commercially in the 1990s. After two decades of production, some groups and individuals remain critical of the technology based on their concerns about possible adverse effects on human health, the environment, and ethical considerations. At the same time, others are concerned that the technology is not reaching its potential to improve human health and the environment because of stringent regulations and reduced public funding to develop products offering more benefits to society. While the debate about these and other questions related to the genetic engineering techniques of the first 20 years goes on, emerging genetic-engineering technologies are adding new complexities to the conversation. Genetically Engineered Crops builds on previous related Academies reports published between 1987 and 2010 by undertaking a retrospective examination of the purported positive and adverse effects of GE crops and to anticipate what emerging genetic-engineering technologies hold for the future. This report indicates where there are uncertainties about the economic, agronomic, health, safety, or other impacts of GE crops and food, and makes recommendations to fill gaps in safety assessments, increase regulatory clarity, and improve innovations in and access to GE technology.

Chimpanzees in Biomedical and Behavioral Research: Assessing the Necessity - Institute of Medicine; National Research Council (The National Academies Press, 2011)
For many years, experiments using chimpanzees have been instrumental in advancing scientific knowledge and have led to new medicines to prevent life-threatening and debilitating diseases. However, recent advances in alternate research tools have rendered chimpanzees largely unnecessary as research subjects. The Institute of Medicine, in collaboration with the National Research Council, conducted an in-depth analysis of the scientific necessity for chimpanzees in NIH-funded biomedical and behavioral research. The committee concludes that while the chimpanzee has been a valuable animal model in the past, most current biomedical research use of chimpanzees is not necessary, though noted that it is impossible to predict whether research on emerging or new diseases may necessitate chimpanzees in the future.

Meeting Critical Laboratory Needs for Animal Agriculture: Examination of Three Options - National Research Council (The National Academies Press, 2012)
Outbreaks of animal disease can have catastrophic repercussions for animal agriculture, the food supply, and public health. Rapid detection, diagnosis and response, as well as development of new vaccines, are central to mitigating the impact of disease outbreaks. The proposed National Bio- and Agro-Defense Facility (NBAF) is a next-generation laboratory for animal disease diagnostics, training, and research that would provide core critical components for defense against foreign animal and zoonotic disease threats. But it will be a major investment with estimated construction costs of 1.14 billion, as currently designed. Meeting Critical Laboratory Needs for Animal Agriculture: Examination of Three Optionsdiscusses the laboratory infrastructure needed to effectively address the threat posed by animal and zoonotic diseases and analyzes three options for creating this infrastructure: building NBAF as currently designed, building a scaled-back version of the NBAF, or maintaining current research capabilities at Plum Island Animal Disease Center while leveraging biosafety level-4 large animal capabilities at foreign laboratories.

Guide for the Care and Use of Laboratory Animals – Spanish Version - National Research Council (The National Academies Press, 2017)

Guide for the Care and Use of Laboratory Animals – Portuguese Edition (The National Academies Press, 1996)

Data and Research to Improve the U.S. Food Availability System and Estimates of Food Loss: A Workshop Summary - Institute of Medicine; National Research Council
The United States Department of Agriculture's (USDA's) Economic Research Service's (ERS) Food Availability Data System includes three distinct but related data series on food and nutrient availability for consumption. The data serve as popular proxies for actual consumption at the national level for over 200 commodities (e.g., fresh spinach, beef, and eggs). The core Food Availability (FA) data series provides data on the amount of food available, per capita, for human consumption in the United States with data back to 1909 for many commodities. The Loss-Adjusted Food Availability (LAFA) data series is derived from the FA data series by adjusting for food spoilage, plate waste, and other losses to more closely approximate 4 actual intake. The LAFA data provide daily estimates of the per capita availability amounts adjusted for loss (e.g., in pounds, ounces, grams, and gallons as appropriate), calories, and food pattern equivalents (i.e., \

Science Breakthroughs to Advance Food and Agricultural Research by 2030 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
For nearly a century, scientific advances have fueled progress in U.S. agriculture to enable American producers to deliver safe and abundant food domestically and provide a trade surplus in bulk and high-value agricultural commodities and foods. Today, the U.S. food and agricultural enterprise faces formidable challenges that will test its long-term sustainability, competitiveness, and resilience. On its current path, future productivity in the U.S. agricultural system is likely to come with trade-offs. The success of agriculture is tied to natural systems, and these systems are showing signs of stress, even more so with the change in climate. More than a third of the food produced is unconsumed, an unacceptable loss of food and nutrients at a time of heightened global food demand. Increased food animal production to meet greater demand will generate more greenhouse gas emissions and excess animal waste. The U.S. food supply is generally secure, but is not immune to the costly and deadly shocks of continuing outbreaks of food-borne illness or to the constant threat of pests and pathogens to crops, livestock, and poultry. U.S. farmers and producers are at the front lines and will need more tools to manage the pressures they face. Science Breakthroughs to Advance Food and Agricultural Research by 2030 identifies innovative, emerging scientific advances for making the U.S. food and agricultural system more efficient, resilient, and sustainable. This report explores the availability of relatively new scientific developments across all disciplines that could accelerate progress toward these goals. It identifies the most promising scientific breakthroughs that could have the greatest positive impact on food and agriculture, and that are possible to achieve in the next decade (by 2030).

Fungal Diseases: An Emerging Threat to Human, Animal, and Plant Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Fungal diseases have contributed to death and disability in humans, triggered global wildlife extinctions and population declines, devastated agricultural crops, and altered forest ecosystem dynamics. Despite the extensive influence of fungi on health and economic well-being, the threats posed by emerging fungal pathogens to life on Earth are often underappreciated and poorly understood. On December 14 and 15, 2010, the IOM's Forum on Microbial Threats hosted a public workshop to explore the scientific and policy dimensions associated with the causes and consequences of emerging fungal diseases.